A history of modern tourism - Zuelow, Eric G. E., ....- (London ; New York, NY : Palgrave in the UK is an imprint of Macmillan Publishers Limited, 2015)
Tourism is one of the largest industries in the world, yet leisure travel is more than just economically important. It plays a vital role in defining who we are by helping to place us in space and time. In so doing, it has aesthetic, medical, political, cultural and social implications. However, it hasn't always been so. Tourism as we know it is a surprisingly modern thing, both a product of modernity and a force helping to shape it.
Includes bibliographical references and index.
Keywords: History; Tourism